Standard or local solar spectrum? Implications for solar technologies studies in the Atacama desert. (November 2018) - Marzo, Aitor; Ferrada, Pablo; Beiza, Felipe; Besson, Pierre; Alonso-Montesinos, Joaquín; Ballestrín, Jesús; Román, Roberto; Portillo, Carlos; Escobar, Rodrigo; Fuentealba, Edward
Abstract: Knowledge of the solar spectrum is essential for the design and study of numerous technologies. Due to the area considered, the harsh conditions and the difficulty for accessing to some zones, information and measurement on local parameters and spectral resource are scarce. This fact, along with the special atmospheric conditions prevailing in Atacama Desert, has led to increasing interest on the part of the solar industry to ascertain the spectral variation respect to that of other places around the world. Considering the standard spectrum for a typical air mass as 1.5, the evaluation of PV module behaviour or device calibration under real conditions can generate a source of uncertainty where spectra may differ. This preliminary paper aims to study the influence of using the standard or local spectra in photovoltaic technologies in Atacama Desert, in order to highlight the necessity for a long-term ground-based measurement campaign. For that purpose, a first approach to the spatio-temporal average of solar spectrum in the Atacama Desert from satellite databases is estimated. Then, local spectra are compared against the Reference Spectra in order to show the differences in studies on solar energy applications. Long-term satellite database information is used to average the atmospheric parameters, such as Aerosol Optical Depth, Ozone, Precipitable Water Vapour, Albedo and Relative Humidity, for the entire Atacama Desert area and is then used to obtain the mean Global tilted Irradiance and Direct plus Circumsolar Irradiance solar spectrum. Finally, to study the influence that the shape of the local spectrum has on the performance of the different solar technologies, the photo-current density of two different solar cell types were studied under Atacama and standard conditions. The results indicate that there are considerable differences with the ASTM G173-03 reference spectra for short wavelengths, especially in the UV spectral range, which is 55% points higher than the reference, which influences in the performance of the solar technologies. Highlights: Mean global and direct spectral irradiances were calculated for Atacama Desert. Differences in shape were found in comparison with the Reference Spectra. Reference Spectra induce errors for PV studies in Atacama Desert. Representative Atacama Desert spectrum led to a PV current gain of 50% in the UV.